Falling into Salvation in Cioran - Joseph Acquisto (Studies in 20th & 21st Century Literature, 2014)
While, at first glance, there seems to be very little room in the thought of E.M. Cioran for the notion of salvation, a closer look reveals that Cioran returns constantly to the vocabulary and the concept of redemption. This article teases out Cioran’s complex use of the topos of salvation throughout his works, with special emphasis on his middle period. I begin by tracing Cioran’s notion of humanity’s fall into time and language, from which he claims there can be no salvation in the traditional Christian sense. Nonetheless, he retains the concept, claiming at various points that there is a kind of salvation to be found in suicide, music, silence, and skepticism. Ultimately, however, each of these provides only false salvation, since the only permanent solution to the problem of existence for Cioran would be either to cease to exist or to lose our human nature in exchange for a plant-like life. Since this is impossible, we are left with our human means of seeking deliverance. While Cioran generally condemns human attempts at creation or procreation, he takes a different approach to the act of writing. In his reflections on writing we see that salvation for Cioran is always temporary, provisional, and threatened by our next bout of lucidity, but at the same time, eternally renewable with each new act of writing.
Keywords: Cioran; salvation; writing; suicide; lucidity